Antibacterial Activity of the Chloroform, Acetone, Methanol and queous Extracts of Algerian Lichens - Rafika, Brakni; Monia, Ali (Jordan Journal of Pharmaceutical Sciences, 2018)
In the current study, we investigated the antibacterial activity of chloroform, acetone, methanol and aqueous extracts of the following lichens: Evernia prunastri (L.) Ach., Ramalina fastigiata (Pers.) Ach. and Cladonia rangiformis Hoffm. The phytochemical analyses of extracts of each species were determined by thin layer chromatography (TLC) and microcrystallization. These extracts were tested in vitro against Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus, Proteus mirabilis and Pseudomonas aeruginosa by the disc diffusion method. The sensitivity of the bacteria to the different lichen extracts is as follows: Staphylococcus aureus is highly sensitive to all extracts and more precisely to the methanolic extract of Evernia prunastri (with a 43 mm inhibition zone), Escherichia coli particularly sensitive to the chloroformic and acetonic extracts of E prunastri and R fastigiata and to the methanolic and aqueous extracts of C rangiformis, Klebsiella pneumonia is insensitive to all lichen extracts, Proteus mirabilis and Pseudomonas aeruginosa are slightly sensitive to certain extracts of R fastigiata. The activity of the lichenic extracts was certainly due to predominant compounds such as lichenic acids (Usnic acid, Evernic acid, Fumarprotocetraric acid and Atranorin), some of which have already proved their antibacterial efficacy. Therefore, these lichens may be used to discover bioactive products that may serve as new sources of natural antimicrobial agents.